GAMBARAN HISTOPATOLOGI PANKREAS MENCIT DIABETES MELLITUS SETELAH PEMBERIAN EKSTRAK ETANOL BONGGOL BUAH NANAS (Ananas comosus (L.) Merr) - Masayu Azizah; Fitri Ramadhanti; Agnes Rendowati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Changes in lifestyle and socio-economy in the current era of globalization can lead to increased rates of non communicable disease, one of which is diabetes mellitus (DM). This study aimed to determine the effect of giving pineapple hump ethanol extract (Ananas comosus (L.) Merr) to the histopathology of pancreatic diabetes mellitus mice induced by alloxan. The test animals used were male white mice with a body weight of 20-30 grams acclimatized for 7 days. The study was divided into five treatment groups, namely group I was the normal group, group II was the negative control group induced by alloxan, group III, IV, and V, namelythe group given pineapple fruit extract ethanol 125 mg / kgBB (P1), 250 mg / kgBB (P2), and 500 mg / kgBB (P3). Tests were carried out through histopathological examination of the pancreatic organ tissue of mice by Hematoxylin Eosin (HE) staining. The parameters measured were the percentage of damage to mice pancreatic cells that experienced necrosis in each group. The results of this study indicate that pineapple hump ethanol extract (Ananas comosus (L.) Merr) has effectiveness in repairing damage to pancreatic cells that experience picnosis, karyorexis, and karololysis because all groups of test preparations have significant differences with the negative control group. Pharmacologically from the 3 doses of ethanol extract of pineapple hump (Ananas comosus (L.) Merr) at a dose of 500 mg / kgBB which is the most optimum in repairing damage to pancreatic cells in diabetes mellitus mice.